2016
DOI: 10.1016/j.rse.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture retrieval over irrigated grassland using X-band SAR data

Abstract: , et al.. Soil moisture retrieval over irrigated grassland using X-band SAR data. Remote Sensing of Environment, Elsevier, 2016, 176, pp.202-218. hal-01336862 1 El Hajj M., Baghdadi N., Zribi M., Belaud G., Cheviron B., Courault D., and 1 Charron F., 2016. Soil moisture retrieval over irrigated grassland using X-2 band SAR data. Remote Sensing of Environment, vol. 176, doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 67 publications
2
99
1
2
Order By: Relevance
“…The soil contribution is a function of the soil moisture and roughness. The vegetation contribution and the attenuation are computed using one or more vegetation parameters, such as the leaf area index, NDVI, and vegetation water content [25][26][27]29,30,49,50].…”
Section: Radar Backscattering Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The soil contribution is a function of the soil moisture and roughness. The vegetation contribution and the attenuation are computed using one or more vegetation parameters, such as the leaf area index, NDVI, and vegetation water content [25][26][27]29,30,49,50].…”
Section: Radar Backscattering Modelmentioning
confidence: 99%
“…The direct vegetation contribution and the attenuation are computed using one or more vegetation descriptors. Several studies showed that the use of the NDVI (Normalized Differential Vegetation Index) as the only vegetation descriptor allows for computation of the vegetation effects on the total backscattered coefficients with good accuracy [26][27][28]. The parametrization of the WCM was provided in several studies for different SAR configurations and crop types [27,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAR remote sensing was widely used to estimate the surface soil moisture in agricultural areas (e.g., [1][2][3][4][5][6][7][8][9]). Over bare soil, the estimation of soil moisture is performed using either a physical (e.g., the Integral Equation Model [10] or statistical (e.g., Baghdadi [11], Dubois [12], and Oh models [13]), with an accuracy better than 6 vol % [3,14,15].…”
Section: Introductionmentioning
confidence: 99%